Accounting for long-term contracts in Algerian Contracting Companies: Practical reality and future challenges - Aouinat, Farid (The International tax journal, 2025)
This study aims to shed light on the theoretical and practical concepts related to long-term contracts concluded at the level of contracting companies, through what the financial accounting system (SCF) is based on, on the one hand, as well as international accounting standards, on the other hand. This research starts within the theoretical framework of defining contracts and clarifying their characteristics, in addition to the accounting treatment. In contrast, the study relies on the practical framework of the descriptive analytical approach. The relevant laws are analyzed and the most important results are drawn that contribute to improving the performance of accounting practices of contracting companies within the Algerian business environment, which has highlighted the existence of challenges related to the clarity of legal texts (accounting and taxation) in addition to practical application in a business environment characterized by instability and slowness in completing projects with long-term contract.